The occurence of fluorescent pseudomonad bacteria in different samples and their antagonism toward Fusarium oxysporum - Nhung, Nguyen Tuyet; Anh, Nguyen Minh; Quynh Mai, Nguyen Thi; Ha, Pham Thanh; Dung, Nguyen Ngoc (Academia Journal of Biology, 2015)
The density of fluorescent pseudomonad bacteria in 47 soil and plant root samples from different places in Vietnam had been investigated. The obtained results showed that, in comparison with the reported date, the number of the fluorescent pseudomonad bacteria in the most samples was low; there were only four natural samples with about 105 cfu/g wet weight. 129 among 170 tested isolated Pseudomonas strains appeared to be antagonistic toward F. oxysporum, but with different activities; 6 isolated Pseudomonas strains have been selected.